Fundamentals of renewable energy processes - Da Rosa, Aldo Vieira (Amsterdam : Elsevier/AP, 2013)
With energy sustainability and security at the forefront of public discourse worldwide, there is a pressing need to foster an understanding of clean, safe alternative energy sources such as solar and wind power. Aldo da Rosa's highly respected and comprehensive resource fulfills this need; it has provided thousands of engineers, scientists, students and professionals alike with a thorough grounding in the scientific principles underlying the complex world of renewable energy technologies. This new third edition of the classic text highlights advances in this vital area, which are proceeding at.
FrontCover; Fundamentals of RenewableEnergy Processes; Copyright Page; Table of Content; Foreword to the Third Edition; Foreword to the Second Edition; Foreword to the First Edition; Acknowledgements; Generalites; 1.1 Units and Constants; 1.2 Energy and Utility; 1.3 Conservation of Energy; 1.4 Planetary Energy Balance; 1.5 The Energy Utilization Rate; 1.6 The Population Explosion; 1.7 The Market Penetration Function; 1.8 Planetary Energy Resources; 1.8.1 Mineral Assets; 1.9 Energy Utilization; 1.10 The Efficiency Question; 1.11 The Ecology Question; 1.11.1 Biological; 1.11.2 Mineral. 1.11.3 Subterranean1.11.4 Oceanic; 1.12 Financing; 1.13 The Cost of Electricity; References; Part I -Heat Engines; A Minimum of Thermodynamics and of the Kinetic Theory of Gases; 2.1 The Motion of Molecules; 2.1.1 Temperature; 2.1.2 The Perfect-Gas Law; 2.1.3 Internal Energy; 2.1.4 Specific Heat at Constant Volume; 2.1.5 The First Law of Thermodynamics; 2.1.6 The Pressure-Volume Work; 2.1.7 Specific Heat at Constant Pressure; 2.1.8 Degrees of Freedom; 2.2 Manipulating Confined Gases (Closed Systems); 2.2.1 Adiabatic Processes; 2.2.1.1 Abrupt Compression; 2.2.1.2 Gradual Compression. 2.2.1.3 p-V Diagrams2.2.1.4 Polytropic Law; 2.2.1.5 Work Done Under Adiabatic Expansion (Close System); 2.2.2 Isothermal Processes; 2.2.2.1 Functions of State; 2.3 Manipulating Flowing Gases (Open Systems); 2.3.1 Enthalpy; 2.3.2 Turbines; 2.3.2.1 Isentropic Processes; 2.4 Entropy and Lossy Systems; 2.4.1 Changes in Entropy; 2.4.2 Reversibility; 2.4.3 Causes of Irreversibility; 2.4.3.1 Friction; 2.4.3.2 Heat Transfer Across Temperature Differences (Heat Transfer by Conduction); 2.4.3.3 Unrestrained Compression, Expansion of a Gas; 2.4.4 Negentropy; 2.5 Distribution Functions. 2.5.1 How to Plot Statistics2.5.2 Maxwellian Distribution; 2.5.3 Fermi-Dirac Distribution; 2.6 Boltzmann's Law; 2.7 Phases of a Pure Substance; 2.8 Symbology; References; Mechanical Heat Engines; 3.1 Heats of Combustion; 3.2 Carnot Efficiency; 3.3 Engine Types; 3.4 The Otto Engine; 3.4.1 The Efficiency of an Otto Engine; 3.4.2 Using the T-s Diagram; 3.4.3 Improving the Efficiency of the Otto Engine; 3.5 Gasoline; 3.5.1 Heat of Combustion; 3.5.2 Antiknock Characteristics; 3.6 Knocking; 3.7 Rankine Cycle; 3.7.1 The Boiling of Water; 3.7.2 The Steam Engine; 3.7.3 And now?; 3.8 The Brayton Cycle. 3.9 Combined Cycles3.10 Hybrid Engines for Automobiles; 3.11 The Stirling Engine; 3.11.1 The Kinematic Stirling Engine; 3.11.1.1 The Alpha Stirling Engine; 3.11.1.2 The Beta Stirling Engine; 3.11.1.3 The Implementation of the Kinematic Stirling; 3.11.2 The Free-piston Stirling Engine; References; Ocean Thermal Energy Converters; 4.1 Introduction; 4.2 OTEC Configurations; 4.3 OTEC Efficiency; 4.4 OTEC Design; 4.5 Heat Exchangers; 4.6 Siting; References; Thermoelectricity; 5.1 Experimental Observations; 5.2 Thermoelectric Thermometers; 5.3 The Thermoelectric Generator.
Includes index.
Keywords: Renewable energy sources; Power (Mechanics); Environmental engineering